Heterosexual transmission and human sexuality in Brazil - Sá, Carlos Alberto Morais de; Moura, Stella Mauraz; Sion, Fernando Samuel (Brazilian Journal of Sexually Transmitted Diseases, 1997)
At che end of 1994, there will be reponed approximarely 60 000 AIDS cases in Brazil and Brazil Ministry of Health estimares between 600 000 co one million cases of HIV-infected individuais mainly concentrared in São Paulo and Rio de Janeiro. The Gaffrée and Guinle University Hospital, Nacional AlDS Referrai Center, Rio de Janeiro, Brazil, is a leading and pioneering AIDS Research Center in South America, which has accumulated more than five thousand HlVpositive individuals since 1983. Sexual transmission is che main category of cransmission in Brazil. Hecerosexual transmission has been expanded si nce 1985. 34.1% of these cases among women and 7.2% among men. Hecerosexual concactconstitute the only risk cacegory of AIDS cases in which the number of female cases exceeds the number of male cases. Since early in the epidemie more men than women have been infected and therefore can infect their femaJe parmers. These differences can reflect more efficient maleco- female rransmission compared with female-tomale as well diversicy of sexual practices among hecerosexual partners in latin american culture more widespread than generally observed. Group sex, heterosexual anoreccal intercourse, bisexuality, lack of fidelity female low self-esteem, risk-averse facet, complete submission to mal e desire, multiple sexual parmers, unprotected sexual concacts are the main componencs of the male-to-female ratio 6 to 1 in Brazil. Hecerosexual cransmission of HIV may reflect latin american sexual praccices and culture. lt is of imporcance to acknowledge real human sexuality to design adequate educacional program that could impact on the epidemie. Healch care provi ders should be alen co the diverse behavior of borh women and men which can be AIDS hot spocs.